Yin-Yang of IL-33 in Human Skin Mast Cells: Reduced Degranulation, but Augmented Histamine Synthesis through p38 Activation - Babina, Magda; Wang, Zhao; Franke, Kristin; Guhl, Sven; Artuc, Metin; Zuberbier, Torsten (Journal of investigative dermatology, 2019)
Mast cells (MCs) are the principal effector cells of IgE-mediated allergy. IL-33 is released by resident skin cells as alarmin upon tissue damage or allergen contact. Owing to their pronounced receptor expression, MCs are important targets of IL-33 action, but consequences for skin MCs are ill-defined, especially upon chronic exposure to IL-33. Mimicking the inflammatory milieu of skin disorders, we found that persistent exposure to IL-33 (over a 5-week period) strengthened skin MC numbers through accelerated cell-cycle progression and restriction of apoptosis. Conversely, IL-33 attenuated degranulation and FcεRI expression, potentially as a feedback to chronic "alarmin" exposure. Interestingly, the negative impact on histamine release was counterbalanced by amplified histamine production. Considering the clinical significance of histamine and scarce information on its regulation, we explored the molecular underpinnings. IL-33 induced swift phosphorylation of p38 and JNK (but not of ERK1/2 or AKT), and stimulated histidine decarboxylase expression. Combining pharmacological inhibition and kinase elimination by Accell-facilitated RNA interference in skin MCs revealed a p38-dependent, but JNK-independent mechanism. Collectively, IL-33 exerts multifaceted effects on cutaneous MCs at a post-maturation stage. The IL-33-skin MC axis may contribute to and balance inflammation in chronic skin disorders.